Ceratorhiza Induction towards ORSV Infection on Viability of Phalaenopsis and Dendrobium - Valentina Dwi Anggita Sari; Mahfut Mahfut; Sri Wahyuningsih; Tundjung Tripeni Handayani (TECHNO: JURNAL PENELITIAN, 2021)
Orchids have a high level of biodiversity, such as Dendrobium and Phalaenopsis, which are epiphytes. Dendrobium can adapt to the condition of where it lives while Phalaenopsis can grow in highlands and depends on sunlight and humidity. Virus infection has become one of the obstacles in cultivating Dendrobium and Phalaenopsis. Efforts to increase fitness and control in Dendrobium and Phalaenopsis cultivation can be done by inducing the plant’s fitness using a mycorrhiza, such as Ceratorhiza. A mycorrhiza is a form of mutualism between fungi and the plant’s root. This research is aimed to give information related to the utilization of Cerathoriza for inducing orchids to suppress Odontoglossum ringspot virus (ORSV) infection, giving it better growth. The research was done in February-March 2021 at Botany Laboratory University of Lampung. A completely randomized factorial design was used on two factors, kind of orchid and mycorrhiza treatment (M), virus (V), and mycorrhiza virus (MV). Variables examined in this research are the amount of living and dead roots and leaves. Data obtained is homogenized using Levene’s test and continued by ANOVA with the significance level of 5% and further testing using Tukey’s test with the significance level of 5%. From this research, it is known that interaction between Phalaenopsis and Dendrobium exists during virus and mycorrhiza administration. It is concluded that Phalaenopsis anabilis is more vulnerable than Dendrobium discolor.